Prospective randomised study of cases of pelvic fracture urethral distraction defects managed by early alignment versus initial suprapubic urinary diversion with delayed urethroplasty - Kumar, Arun; Kaur, Gunjeet; Singh, Krishna Kant; Pahwa, H. S.; Kumar, Awanish; Pratap, Dhirendra; Agrawal, Priyanka (International Journal of Research in Medical Sciences, 2020)
Background: In complex pelvic fracture urethral distraction defects (PFUDD), early management prevents incidence of devastating complications such as urinary incontinence, restenosis and urethra cutaneous fistula. The aim of the present study was to study the outcome of patients with PFUDD undergoing early alignment (either by rail roading or endoscopic) compared with initial suprapubic urinary diversion with delayed urethroplasty. Methods: This was a prospective randomized study done at KGMU, Lucknow; having PFUDD during the period from June 2014 to July 2017. Patients with PFUDD were randomized in to two groups. Group A included 22 patients and managed by supra pubic cystostomy followed by delayed urethroplasty. Group B included 23 patients and managed by primary alignment by rail-roading and early endoscopic alignment. Patients were followed up after 6 weeks, 3 months and 6 months for measuring the primary and secondary outcomes during follow up. Results: The most common age group that sustained pelvic fracture urethral distraction defects injury are male of 21-40 years. In group A, stricture was present in all patients at 6 weeks post-surgery. Open urethroplasty was done at 3 months in 60% and 10% patients at 6 months. In group B, stricture was present in 80% at 6 weeks, 40% at 3 months and 10% at 6 months. The incidence of ED in group A at 6 weeks, 3 months, was 25% patient which reduced to 20% at 6 months. In group B, ED was present in 30% patients 6 weeks, 3 months and which reduced to 25% at 6 months. No incontinence was observed in both groups. Conclusions: Primary realignment has significant benefits compared to SPC as realignment approach is associated with a 50%-55% decrease in stricture formation.